Vitamin D status in youth with type 1 and type 2 diabetes enrolled in the Pediatric Diabetes Consortium (PDC) is not worse than in youth without diabetes. Issue 8 (26th November 2015) - Wood, Jamie R.; Connor, Crystal G.; Cheng, Peiyao; Ruedy, Katrina J.; Tamborlane, William V.; Klingensmith, Georgeanna; Schatz, Desmond; Gregg, Brigid; Cengiz, Eda; Willi, Steven; Bacha, Fida; Beck, Roy W.; et al.
Abstract : Objective: To describe vitamin D levels and prevalence of vitamin D sufficiency, insufficiency and deficiency in a large, ethnically/racially diverse population of youth with type 1 diabetes (T1D) and type 2 diabetes (T2D) in comparison to national data and examine the associations between clinical/demographic factors and vitamin D levels. Methods: 25‐hydroxy vitamin D (25OHD) levels were measured in 215 youth with T1D and 326 youth with T2D enrolled in the Pediatric Diabetes Consortium (PDC). These levels were compared with those of youth of the same age without diabetes from the 2005–2006 NHANES Survey. Results: Vitamin D deficiency (<21 ng/mL) was present in 36% of PDC participants, and insufficiency (21–29 ng/mL) was present in an additional 34%. About 36% of age‐matched youth in the NHANES Survey were vitamin D deficient and an additional 41% were insufficient. Deficiency or insufficiency varied by race/ethnicity, being highest in African–Americans (86%), intermediate in Hispanics (77%), and lowest in non‐Hispanic whites (47%). Lower 25OHD levels were observed in African–American and Hispanic youth, during fall and winter, and at sites in the northern United States (all p‐values < 0.001). Youth with T2D had significantly lower 25OHD levels than youth with T1D (p < 0.001), but this difference was largely eliminated after adjusting for race/ethnicity and socio‐economic status. Conclusions: Vitamin D deficiency/insufficiency is present in a substantial proportion of youth with diabetes, particularly minorities, but the prevalence appears similar to that in youth without diabetes. Further studies are needed to examine whether youth with diabetes would benefit from vitamin D supplementation.